Quantifying coastal cliff retreat, sediment volume, and dynamics using photogrammetry and geospatial analysis in the Pénestin Peninsula, France - David Menier; Romain Le Gall; Manoj Joseph Mathew; Benjamin Sautter; Mu. Ramkumar; Effi Helmy Ariffin; Glen Bulot; Franto Novico; Guilhem Estournès; Céline Le Mignant (Geomorphology, 2025)

Unraveling the enigma: chronic kidney disease of unknown etiology and its causative factors with a specific focus on dissolved organic compounds in groundwater—reviews and future prospects - Madhumitha Kumaresan; Anjali Vijayan; Mu. Ramkumar; Neena Elezebeth Philip (Environmental Geochemistry and Health, 2024)

A Graph Convolutional Network Approach to Qualitative Classification of Hydrocarbon Zones Using Petrophysical Properties in Well Logs - B. Venkateshwaran; Mu. Ramkumar; Numair Ahmed Siddiqui; AKM Eahsanul Haque; G. Sugavanam; A. Manobalaji (Natural Resources Research, 2024)

Physico-chemical Properties of the Vettar Estuarine Waters, Cauvery Basin, Southern India: Implications for Environmental Management - Deepthi Nanjappa; K P Devaganga; Mu Ramkumar; R Nagarajan; K Balasubramani (Thalassas: An International Journal of Marine Sciences, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Facies, depositional environments, and anatomy of the Subis build-up in Sarawak, Malaysia: implications on other Miocene isolated carbonate build-ups - Bing Bing Saw; Markus Schlaich; Michael C. Pöppelreiter; Mu. Ramkumar; Peter Lunt; Jose Antonio Gamez Vintaned; Syed Haroon Ali (Facies, 2019)

Stable isotope analyses of belemnites from the Kachchh Basin, western India: paleoclimatic implications for the Middle to Late Jurassic transition - Matthias Alberti; Franz T. Fürsich; Dhirendra K. Pandey; Mu. Ramkumar (Facies, 2012)

87Sr/86Sr anomalies in Late Cretaceous-Early Tertiary strata of the Cauvery basin, south India: Constraints on nature and rate of environmental changes across K-T boundary - Mu Ramkumar; Doris Stüben; Zsolt Berner; Jens Schneider (Journal of Earth System Science, 2010)

Announcement - Mu. Ramkumar (Journal of the Indian Society of Remote Sensing, 2006)